CODESRIA Bulletin Online, No. 8, September 2025 - 2025 CODESRIA Meaning-Making Research Initiatives (MRI) Selection Report - Programme, Research; Secretariat, CODESRIA (CODESRIA Bulletin, 2025)
The Meaning-making Research Initiative (MRI), launched in July 2017, serves as the Council’s primary vehicle for advancing research in the humanities and social sciences. In November 2024, the fourth edition of MRI was launched and three categories of calls for applications were disseminated in English, French and Portuguese—MRI General Fellowship (GF), MRI Special Fellowship for Female Scholars (SFFS) and Advanced Senior Research Fellowship (ASRF). These calls were specifically designed to align with the objectives articulated in the 2023–2027 Strategic Plan. This report provides an account of the selection process. It is organised into six sections: Analysis of Applications Selection Process Selected Proposals Evaluator Insights Recommendations for Future MRI Implementation Annex: List of Approved Projects. ANALYSIS OF APPLICATIONS At the close of the calls for applications, a total of 405 applications were received across all three categories: GF, SFFS and ASRF. Following a preliminary screening, 68 applications were excluded on the grounds that they were of extremely poor quality, had an incomplete set of submissions or did not have doctoral qualification. This screening process reduced the number of eligible applications to 337, which constitutes the basis for the analysis below. Applications received: Among the 337 eligible applications, 199 were submitted under the MRI GF category, comprising 105 group and 94 individual projects. An additional 133 applications were received under the SFFS, and 5 applications were submitted for the ASRF. Breakdown by gender: The applicant pool demonstrates a strong female representation, with 66% of applicants identifying as women and 34% as men, as reflected in the accompanying graph. Gender representation of coordinators: Of the 199 proposals submitted under the MRI General category, 49 were coordinated by women and 150 by men. All 133 proposals submitted under the SFFS were coordinated by women. For the ASRF, all 5 proposals received were from male scholars. Language distribution of proposals: The graph illustrates the distribution of proposals by language. Of the 337 submissions, 218 were written in English, 99 in French and 20 in Portuguese. Regional distribution: As shown in the following graphic, the regional distribution of the 337 applications depicts a pronounced concentration from West Africa, which accounts for 55% of the total submissions. East Africa follows with 15%, while southern and Central Africa each represent 14%. North Africa comprises the remaining 2% of eligible submissions. National-level disparities: Map 1 highlights significant disparities in national representation among eligible applications. Notably, Nigeria accounts for over 200 applications, while many other countries recorded fewer than 10 or none at all. The applications have been classified into five categories: Very Low (1–10 applicants) Low (11–30) Medium (31–80) High (81–150) Very High (151–210). Map 1: MRI 2025 Geographical Representation of Applicants This distribution highlights a persistent geographical imbalance in participation across various African countries. The Council was aware of this imbalance, having noted a similar pattern in previous iterations of the MRI. To address the challenge, a targeted dissemination campaign was launched in December 2024, reaching 170 researchers, university administrators, academic leaders and research centres in the humanities and social sciences across the continent. Additional efforts included direct outreach to relevant faculties and departments, as well as special appeals to former MRI grantees to help spread the Call for Applications within their networks. The Council also organised an information session on the MRI grants, convened virtually on 24 January 2025, with the participation of over 100 people from multiple countries. Despite these initiatives, the geographic spread of applications remains uneven. This emphasises the need for more tailored and sustained strategies to engage with regions that remain underrepresented. It could be useful to enhance access to CODESRIA research programmes by organising periodic in-person or virtual meetings and by establishing focal points within universities and research institutions across the continent, where appropriate. Qualified resource persons at these focal points could proactively support potential candidates in accessing relevant information. Where appropriate, support materials (posters, brochures, etc.) might also be shared to aid dissemination. This approach could help strengthen the visibility and consistency of CODESRIA’s activities, encouraging broader participation of young scholars, particularly from underrepresented countries and regions. SELECTION PROCESS The selection process was conducted in three phases. The first phase involved a comprehensive update of the evaluator databases for English, French and Portuguese speakers. This update was carefully aligned with the thematic focus of the manuscripts, and identified gaps in reviewer expertise and the performance of evaluators in undertaking their work in previous MRI editions. Reviewers were selected based on academic standing and professional qualifications and were balanced geographically and linguistically to ensure adequate representation and coverage of the range of applications received. Nonetheless, in certain cases, there were challenges in aligning manuscript themes with the specific areas of expertise of the available reviewers. In the second phase of the selection process, applications submitted under the GF and SFFS categories were assigned to 46 external evaluators. Applications under the ASRF category were reviewed by 2 external evaluators. Each reviewer was responsible for providing a critical appraisal of the proposals, focusing on key elements such as conceptual and methodological soundness, originality and innovativeness. Reviewers also evaluated whether the proposed work had been previously published, its relevance to advancing research in specific areas and its contribution to advancing scholarly debates. It is important to reiterate that assessments were aligned with the thematic priorities outlined in the Strategic Plan. They emphasised the potential of each project to contribute original knowledge in line with the spirit of meaning-making as articulated in the framing document of the MRI. To ensure coherence in evaluation standards, reviewers were provided with a comprehensive guideline detailing evaluation criteria that aimed to standardise the evaluations as much as possible. All proposals were evaluated under a double-blind peer-review system. The aim was to uphold impartiality and attain academic rigour. In addition to providing written feedback on each individual proposal, reviewers were required to submit an overall report summarising their thinking about the set of applications they assessed. A consolidated report, synthesising the full body of reviewer feedback, will be produced at a later stage. Overall, while evaluators acknowledged improvements in the quality of writing, they highlighted a persistent gap between the high standards expected under the MRI scheme and the substantial number of proposals that were substantively weak and poorly constructed. Once again, this is a persisting challenge that the Council should address. Previous attempts to address the weaknesses have hinged on the assumption that the challenge is located at the level of graduate training within source universities where the applicants come from. The evaluation process took longer than initially anticipated, largely because of delays from some evaluators who, despite initially accepting the assignment, did not respond to repeated reminders. This necessitated the identification and recruitment of alternative reviewers with appropriate academic profiles to ensure the timely completion of the review process. In the third phase, a joint committee comprising members from the Research and TGF programmes at the Secretariat was convened to review the evaluation reports and conduct the necessary arbitration. The selection process considered multiple criteria, including the quality of proposals (as reflected in scores and reviewer feedback), regional and linguistic balance and thematic relevance. In this exercise, the quality of the application, as reflected by the scores assigned by external reviewers, remained a sacrosanct variable. SELECTED PROPOSALS The CODESRIA Secretariat sub-committee selected the proposals deemed most competitive based on the outlined criteria. The selected proposals were broken down as follows: MRI ASRF: Of the 5 proposals received, 4 were written in English and 1 in French, all submitted by male scholars. The committee selected 1 proposal in English. Priority was given to those proposals with the potential for intellectual leadership and innovative theoretical and methodological contributions of the application to the field of study. MRI SFFS: Of the 133 submissions received, 98 were written in English, 33 in French and 2 in Portuguese. The committee selected 16 proposals in this category: 14 in English and 2 in French. Proposals submitted in Portuguese were not recommended, because they did not meet the required quality standards. MRI GF: Of the 198 proposals submitted, 115 were written in English, 65 in French and 18 in Portuguese. The committee recommended 15 proposals in English, 5 in French and 2 in Portuguese. Map 2: Geographical Representation of Selected Applicants The geographical distribution of the nationalities of selected applicants in Map 2 shows West Africa with 41% representation, followed by East Africa (26%), southern Africa (11%), Central Africa (7%) and North Africa (7%). The classification scale applied to the selected projects ranges from very few (1–2) to low (3–4), medium (5–6), high (7–8) and very high (9– 11). As highlighted by the mapping, this distribution indicates that the projects are concentrated in a limited number of countries, with West Africa clearly leading in terms of representation and North Africa being almost absent. The data indicates that some regions and countries consistently secure more successful projects, whereas others remain underrepresented. This imbalance may be linked to a range of factors, including demography and available resources for intellectual engagement. Of course, there are also colonial legacies that have historically influenced access to higher education and quality training. EVALUATOR INSIGHTS As noted above, a total of 46 external evaluators participated in the double-blind review process. Reviewers were selected from CODESRIA’s database for their areas of expertise and scholarly experience. On average, each evaluator was assigned 15 proposals. According to a significant number of reviewers, the overall quality of the proposals was moderate, with only a few demonstrating high academic merit. The proposals covered a range of themes, including the informal economy, gender inequalities, entrepreneurship, economic governance, coloniality, endogenous knowledge/social transformation and climate/ ecological topics. Most aligned well with the Council’s priority and cross-cutting themes, with a notable number focusing on ecology and environmental subjects. Several evaluators noted that many proposals met the expected standards of theoretical and methodological rigour, offered fresh perspectives and showed strong potential for advancing knowledge. One evaluator observed: Most proposals demonstrate well-defined theoretical frameworks, including feminist theory, socio-ecological models and mixed-methods designs, enhancing the credibility and rigour of their studies. Similarly, another evaluator remarked: The quality of the proposals was generally good, except for a few, as reflected in the scores awarded. Evaluators also highlighted the high quality of several proposals submitted under the special call for female scholars. These proposals were strong in terms of thematic focus, problem definition, research questions, theoretical framing and literature review. As one Portuguese speaking evaluator noted: De uma forma geral, os projetos apresentados no quadro da chamada especial ‘Mulheres Académicas’ apresentam um elevado grau de maturidade. Com efeito, tanto as temáticas, a definição do problema de pesquisa, as questões e os objetivos de investigação, o modelo teórico de análise e a revisão de literatura demonstram uma maturidade significativa. Todos os projetos são relevantes tanto do ponto vista teórico quanto empírico, no sentido de poder oferecer importantes inputs ao processo de definição de políticas públicas.[1] Similarly, a French-speaking evaluator noted: Dans l’ensemble, les propositions sont bien rédigées, pertinentes et solidement argumentées. Elles posent des problématiques claires et actuelles, mobilisent des approches méthodologiques appropriées, et présentent des stratégies de mise en œuvre réalistes. Les propositions émanant de l’appel spécial aux femmes abordent des thématiques cruciales en lien avec l’autonomisation économique, sociale et politique des femmes et contribuent à une meilleure intégration des enjeux de genre dans la recherche.[2] The citations above highlight the strength of the project designs, noting both their theoretical and empirical relevance and their potential to make valuable contributions to the formulation of public policy. The reviewers identified several limitations in other proposals, especially their weakness with respect to meeting the expected quality criteria. Although the submissions broadly covered the geographic diversity of the continent, major weaknesses were observed in addressing core conceptual questions. One evaluator remarked that, despite the overall good quality of several submissions, some lacked clarity or conceptual depth. This was echoed in several reviews, including one written in French: Dans l’ensemble, les propositions sont bien rédigées, pertinentes et solidement argumentées. Elles posent des problématiques claires et actuelles, mobilisent des approches méthodologiques appropriées et présentent des stratégies de mise en œuvre réalistes. Cependant, une partie de ces projets présente des faiblesses, en particulier au niveau de leurs cadres théoriques et méthodologiques. Cette faiblesse fragilise davantage leurs objectifs.[3] In short, these comments reflect a general sense of satisfaction with the quality of many submissions, while also underscoring areas for improvement. There were concerns raised about some proposals, particularly regarding a lack of innovation and overall quality. According to the evaluation reports, several proposals were repetitive in their treatment of themes and lacked clarity. Additionally, some presented weak methodological sections and, in most cases, failed to align with the core focus of the MRI calls. As one evaluator observed: The proposals varied in strength when it came to conceptualisation; there were many I could see had either been submitted elsewhere or were not tailored to this call. As a result, some of the literature reviews were patchy. Regarding meaning-making, I expected strong proposals to clearly articulate what kind of meaning they were addressing or concerned with. Most proposals were silent on the historical context of the phenomena they examined. They came across as addressing recent issues, whereas many of the topics require deeper engagement with historical roots. In general, while the themes were considered ‘attractive’ and relevant as research topics—particularly in relation to female scholars—some proponents still struggled with demonstrating a good understanding of how to frame questions for conducting cutting-edge research. Compared to the previous MRI edition (2023–2024), there was a slight improvement in the technical and linguistic quality of the proposals. Moreover, the inclusion of more innovative approaches contributed to a higher number of proposals being recommended for support. From a comparative perspective, applicants based in West Africa show strong participation relative to other regions of the continent. This trend reflects a pattern observed in previous editions of MRI, dating back to the inaugural session in 2017. It also reflects a pattern in other major CODESRIA programmes. Of course, the percentage is bumped up primarily because of the generally higher level of participants from Nigeria and Cameroon. Finally, some evaluators shared comments highlighting key challenges and offering recommendations. Notably, a recurring concern is the insufficient valorisation of African scholarly production. In several proposals—including those recommended for selection—African scholarly production remains underutilised. Greater anchoring in research conducted on the continent and in the target countries would significantly strengthen the theoretical foundations of the work This, for instance, is what a French-speaking evaluator observed: Un autre constat est le manque de valorisation des savoirs produits sur le continent. Dans la majorité des propositions et y compris pour celle dont je recommande qu’elle soit sélectionnée, la production scientifique africaine est souvent totalement ignorée. Les cadres théoriques, l’état de l’art, la revue des hypothèses concurrentes gagneraient à trouver un ancrage plus important dans les recherches conduites sur le continent et dans les pays ciblés.[4] (Translation from the original French) The evaluators also highlighted the need for more systematic dissemination of information regarding the institution’s programmes and grants, beyond the Council’s website. To enhance visibility and outreach, broader communication strategies—such as the use of posters, flyers and other public communication materials—should be developed and actively promoted to ensure wider dissemination of CODESRIA’s work and objectives, particularly in regions where the Council’s activities are less known and where technology is not an efficient means of support. In this regard, an evaluator suggested that the private sector could serve as a potential funding source for the Council, while also offering opportunities to strengthen CODESRIA’s presence in those regions. The reviewers acknowledged the relevance of the themes presented in the proposals but highlighted significant weaknesses in theory and methodology. They pointed to a lack of strong pan-African and decolonial perspectives, which are essential for institutions like CODESRIA. Several projects lack positionality and do not address reflexivity. They tend to be quite ‘outward-looking’ in how they engage with the literature produced in Africa and by Africans. The authors often fail to critically reflect on their own positionality as intellectuals, on their contexts of origin during the research process and on the complexity of the realities with which they engage. This has a direct impact on data collection and, consequently, on the analysis and findings of the research, which end up being less relevant, or ‘extraverted’. They often rely on colonial scientific frameworks, portraying researchers as elite knowledge holders not very keen on engaging with communities or co-producing knowledge. The reviewers stressed the importance of incorporating local and Indigenous knowledge to reflect local identities and urged African researchers to express their political subjectivities more openly. While the use of oral sources in some projects was commendable, the methodological sections of these studies are overall weak and need to clearly conceptualise and explain the research process. Despite the challenges highlighted by the evaluators in their assessments, it is fair to acknowledge the Council’s continued efforts to enhance the academic quality of African scholars through initiatives such as the MRI. CODESRIA plays a vital role in fostering critical, context-driven and transformative research across the continent. RECOMMENDATIONS FOR FUTURE MRI IMPLEMENTATION Several evaluators’ reports and comments offer suggestions that could be considered for future MRI calls. Among these are: Provide targeted feedback and capacity-building opportunities to applicants: This could include a pre-submission workshop to strengthen framing of their research proposals and methodology, thereby increasing the pool of competitive proposals. Improvement to avoid delays in the evaluation process: In future cycles, we may wish to consider strategies for mitigating delays. Some reviewers missed submission deadlines or did not respond, requiring replacements and extending the evaluation timeline beyond the original target of April 2025. As strategies, we could: Enhance the reviewer selection: Prioritise reviewers with proven timely submission records. 2- Adjust the schedule: Build in additional time between the official deadline and the final cut-off, providing space for late submissions without affecting the overall schedule. 3- Expand the reviewer pool: Maintain a reserve list of backup reviewers who can be promptly engaged if a primary reviewer withdraws or fails to deliver. Enhance outreach to underrepresented countries: While targeted outreach efforts increased applications from some underrepresented countries, certain regions and countries remain absent. This suggests the need to explore additional approaches to raise awareness and address access barriers that affect participation. Strengthen the application screening process by introducing an initial eligibility check before full review and implement an automated system to flag multiple submissions or ineligible applicants. Additionally, consider reinforcing compliance through more visible reminders of the eligibility rules, both in the call for applications and during all applicant communications, to reduce the number of non-compliant submissions. Consider developing and sharing a standardised proposal development protocol, including clear templates and step-by-step guidance, to help applicants meet the programme’s eligibility and quality standards before submission. Strengthen partnership and direct coordination between CODESRIA and African academic research institutions. Develop connectivity between academic research institutions, the public sector and the private sector. CODESRIA could undertake outreach efforts to the public and private sectors through the Facilitator Focal Points. Consider implementing targeted support for applicants submitting proposals in underrepresented languages, such as Portuguese and Arabic, including translated guidelines, to help reduce language disparities and encourage broader participation. ANNEX: APPROVED PROJECTS MRI ADVANCED SENIOR RESEARCH FELLOWSHIP (Please see PDF file). [1] general, the projects submitted under the special call ‘Female Scholars’ display a high level of maturity. The themes, research problem definition, questions and objectives, theoretical framework and literature review all demonstrate significant depth. All the projects are relevant both theoretically and empirically, with the potential to provide valuable inputs for public policy formulation. ((Translation from the original Portuguese) [2] In general, the proposals are well written, relevant and strongly argued. They present clear and timely research problems, employ appropriate methodological approaches, and propose realistic implementation strategies. The proposals submitted under the special call for female scholars address crucial themes related to the economic, social and political empowerment of women and contribute to a better integration of gender issues in research. (Translation from the original French) [3] In general, the proposals are well written, relevant and strongly argued. They present clear and timely research problems and appropriate methodological approaches, and propose realistic implementation strategies. However, some of these projects show weaknesses, particularly in their theoretical and methodological frameworks, which further undermines their objectives. (Translation from the original French) [4] Another observation is the lack of recognition and use of knowledge produced on the continent. In most proposals, including the one I recommend for selection, African scientific output is often completely overlooked. The theoretical frameworks, state of the art and review of competing hypotheses would benefit from being more strongly anchored in research conducted on the continent and in the targeted countries. (Translation from the original French)